Diastolic dysfunction and cognitive impairment: Neuropsychiatry and behavioral neurology: Novel risk factors and novel approaches to risk in dementia. (7th December 2020) - Parker, Alicia S.; Himali, Jayandra J; Beiser, Alexa S.; Short, Meghan I.; Kautz, Tiffany; Vasan, Ramachandran S.; Seshadri, Sudha
Abstract: Background: The relationship between diastolic dysfunction and cognition is undefined. Diastolic dysfunction is common, disproportionately affects females, and is increasing in the community. While earlier studies suggested that management of diastolic dysfunction did not improve cardiovascular mortality, there is increasing evidence that diastolic dysfunction affects patient outcomes. Our clinical observation is that patients with diastolic dysfunction tend to have increased white matter hyperintensities on imaging. If diastolic dysfunction is found to be associated with cognitive impairment, that would suggest diastolic dysfunction is a novel modifiable risk factor for the development of dementia. Method: Echocardiographic, MRI and neuropsychological data collected by the Framingham Heart Study, Offspring Cohort, at Exam 8 was reviewed. Diastolic measures were related to MRI measures of total cranial brain volume, hippocampal volume and white matter hyperintensities, and to neuropsychological evaluations. Result: Data from 1438 participants (Figure 1) showed that increasing E/E' ratio, indicating increasing diastolic dysfunction, was associated with increased executive function impairment in the Similarities (β±SE:‐0.29±0.09, p<0.002) and FAS Phonemic Fluency (‐1.27±0.33, p<0.001) tasks. Participants with moderate to severe diastolic dysfunction performed more poorly on Logical Memories (‐0.70±0.34, p<0.036) and FAS Phonemic Fluency (‐2.75±1.11, p<0.014), and trended towards increased impairment on Similarities (‐0.59±0.30, p<0.052) (Table 1). Data from 1217 participants (Figure 2) showed that those with mild diastolic dysfunction trended towards increased white matter hyperintensities (0.11±0.07, p<0.105); participants with moderate‐to‐severe diastolic dysfunction had increased white matter hyperintensities (0.30±0.09, p<0.001) (Table 2). Data from 1415 participants showed that increasing E/E' ratio was associated with increased incident mild cognitive impairment (HR 1.29 [95%CI: 1.01, 1.66], p<0.043; Table 3). Conclusion: Diastolic dysfunction was associated increased incident mild cognitive impairment. Increased diastolic dysfunction was associated with impaired executive function and verbal memory on neuropsychological testing, along with increased cerebral small vessel disease as demonstrated by white matter hyperintensities on MR imaging. As cerebral small vessel disease clinically presents with executive function impairment, these results align well. An amnestic impairment was also seen, such as can occur in Alzheimer's disease. This study suggests that diastolic dysfunction is a novel modifiable risk factor for the development of dementia. Further research examining management of diastolic dysfunction on cognitive outcomes would be of benefit.